Endogenous Appropriability - Gans, Joshua S.; Stern, Scott (American Economic Review, 2017)
Most approaches to entrepreneurship assume that entrepreneurial control over their inventions is critical for success and, in turn, for incentives. Such control is usually supported by regulations that protect intellectual property including patents, copyrights, and trade secrets. Each give the entrepreneurs control over who can appropriate value from their activities. However, we note that another, distinct path exists for appropriation by entrepreneurs' execution. Execution forgoes the formal protection from control instead of a more rapid approach to market in the pursuit of capabilities that will allow entrepreneurs to compete with others in the future rather than block their activities per se. We characterize the conditions under which one path is preferred to another and present evidence from university startups delineating the tradeoffs at the heart of our theoretical approach.